Manajemen Kepala Sekolah dalam Meningkatkan Kompetensi Profesional Guru (Studi pada Madrasah Tsanawiyah (MTs) Kecamatan Lapang Kabupaten Aceh Utara) - Bahri, Saiful; Armanda, Dicky; Kurniawan, Rudi (Universitas PGRI Semarang, 2022)
The purpose of this study is to describe the management, obstacles and efforts of the principal in improving the professional competence of teachers at Madrasah Tsanawiyah (MTS) Lapang District, North Aceh Regency. This study uses a descriptive qualitative research method using techniques to obtain data through observation, interviews, and documentation. This study used 10 informants who were determined purposively consisting of the Principal of Madrasah Tsanawiyah (MTS) Lapang District, Deputy Principals and their staff, some teachers and students of Madrasah Tsanawiyah (MTS) Lapang. The results showed that the principal's management in improving the professional competence of teachers at Madrasah Tsanawiyah, Lapang District, North Aceh Regency was very effective. The principal's management is to improve the teaching abilities of teachers, optimize the utilization and use of media and educational facilities, establish good cooperation with the community, apply strict discipline for students and teachers and carry out regular supervision of teachers and students. Obstacles in improving the professional competence of teachers at Madrasah Tsanawiyah, Lapang District, include: limited flow of funds and incomplete facilities and infrastructure. The principal's effort in this case is to look for opportunities to increase the injection of funds to schools, either through donors, local governments or the central government. The principal strives for the teaching staff to use the media facilities and infrastructure as much as possible even though they are limited.